Laser‐heating system for high‐pressure X‐ray diffraction at the Extreme Conditions beamline I15 at Diamond Light Source - Anzellini, Simone; Kleppe, Annette K.; Daisenberger, Dominik; Wharmby, Michael T.; Giampaoli, Ruggero; Boccato, Silvia; Baron, Marzena A.; Miozzi, Francesca; Keeble, Dean S.; Ross, Allan; Gurney, Stuart; Thompson, Jon; et al. (Journal of synchrotron radiation, 2018)
In this article, the specification and application of the new double‐sided YAG laser‐heating system built on beamline I15 at Diamond Light Source are presented. This system, combined with diamond anvil cell and X‐ray diffraction techniques, allows in situ and ex situ characterization of material properties at extremes of pressure and temperature. In order to demonstrate the reliability and stability of this experimental setup over a wide range of pressure and temperature, a case study was performed and the phase diagram of lead was investigated up to 80 GPa and 3300 K. The obtained results agree with previously published experimental and theoretical data, underlining the quality and reliability of the installed setup. A double‐sided, off‐axis laser‐heating system for monochromatic X‐ray diffraction experiments using a diamond anvil cell has been installed at beamline I15 at Diamond Light Source. Measurements of the pressure–temperature phase diagram of Pb demonstrate the reliability of the setup and the high quality of the data.